216k views
2 votes
If f(x) = 4x ^ 2 and g(x) = x + 1 , find (fg)(x) ).

a. 4x(x)
B. 4x ^ 3 + 4x ^ 2
C. 4(x + 1) ^ 2
D. 4x ^ 2 + 1

User TerDale
by
4.5k points

2 Answers

3 votes

Answer:


\boxed{\sf \ C \ is \ the \ correct \ answer \ ! \ }

Explanation:

fog(x)=f(g(x))

so it comes


f(g(x))=f(x+1)=4(x+1)^2

so C is the correct answer

User Marshally
by
4.7k points
4 votes

Answer:

Option B

Explanation:


f(x) = 4x^2\\g(x) = x+1

Multiplying both will give us:


(fg)(x) = 4x^2(x+1)

=>
(fg)(x) = 4x^3+4x^2

User Dajuan
by
5.1k points